Understanding classes using XRay views - Arévalo, Gabriela Beatriz (2003)
Understanding the internal workings of classes is a key prerequisite to maintaining an object-oriented software system. Unfortunately, classical editing and browsing tools offer mainly linear and textual views of classes and their implementation. These views fail to expose the semantic relationships between the internal parts of a class. We propose XRay views —a technique based on Concept Analysis— which reveal the internal relationships between groups of methods and attributes of a class. XRay views are composed out of elementary collaborations between attributes and methods and help the engineer to build a mental model of how a class works internally. In this paper we present XRay views, and illustrate the approach by applying it to three Smalltalk classes: OrderedCollection, Scanner, and UIBuilder. Keywords: Class Understanding, Concept Analysis, Logical Views.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 12-03-2008)
Proceedings of 2nd International Workshop on MASPEGHI 2003 (ASE 2003), 9–18, IEEE Computer Society Press, CRIM-University of Montreal (Canada), October 2003.
Keywords: INGENIERÍA HUMANA; IBM LOTUS SAMETIME; FORTRAN